Cover Feature: Diferrate [Fe2(CO)6(μ‐CO){μ‐P(aryl)2}]− as Self‐Assembling Iron/Phosphor‐Based Catalyst for the Hydrogen Evolution Reaction in Photocatalytic Proton Reduction—Spectroscopic Insights (Chem. Eur. J. 60/2018). Issue 60 (24th October 2018) - Fischer, Steffen; Rösel, Arend; Kammer, Anja; Barsch, Enrico; Schoch, Roland; Junge, Henrik; Bauer, Matthias; Beller, Matthias; Ludwig, Ralf
Abstract : Understanding the mechanism of photocatalytic water reduction is essential for the development of effective catalysts. A new, self‐assembling, and sulfur‐free [FeFe]‐hydrogenase mimic, which shows good catalytic activity, is described. The action of the visible‐light‐driven iron catalyst within the cycle of H2 production from water is monitored by a combination of in‐situ spectroscopic methods. More information can be found in the Full Paper by R. Ludwig et al. onpage 16052 .